Differential Effects of Human SP-A1 and SP-A2 on the BAL Proteome and Signaling Pathways in Response to Klebsiella pneumoniae and Ozone Exposure - Wang, Guirong; Umstead, Todd M.; Hu, Sanmei; Mikerov, Anatoly N.; Phelps, David S.; Floros, Joanna (Frontiers in Immunology, 2019)
Surfactant protein A (SP-A) plays critical roles in host defense, regulation of inflammation and surfactant metabolism in the lung. The human SP-A locus consists of two functional genes, SFTPA1 and SFTPA2 encoding surfactant proteins SP-A1 and SP-A2, respectively. Structural and functional differences exist between SP-A1 and SP-A2 in vitro and in vivo. Ozone is a major air pollutant with a negative impact on many biological processes. In this study we used humanized transgenic (hTG) SP-A1 and SP-A2 mice, and SP-A KO mice to study in vivo effects of SP-A1 and SP-A2 on the bronchoalveolar lavage (BAL) proteomic profile and associated signaling pathways in response to ozone or filtered air (FA) exposure and Klebsiella pneumoniae infection. The BAL samples were harvested 24 h after ozone (2 ppm for 3 h) or FA exposure and infection and analyzed by two-dimensional difference gel electrophoresis (2D-DIGE) and MALDI-ToF/ToF. We found: that (1) Ozone exposure, but not infection, is a major factor for increases in total BAL protein content. (2) A total of 36 proteins were identified, accounting for 89.62% of the BAL proteins resolved by the 2D-DIGE system. (3) The number of proteins in which levels were altered more than 25% following infection and FA exposure was: SP-A2 > SP-A1 > KO for male mice, and SP-A2 ≈ SP-A1 > KO for female mice. (4) The number of proteins with more than 25% increase/decrease after ozone exposure and infection was: SP-A2 > SP-A1 ≈ KO, with the majority being increases in male mice and decreases in female mice. (5) Eleven out of the 36 proteins, including annexin A5, glutathione S-transferase A4, SP-A1/SP-A2, and 14-3-3 zeta protein, exhibited significant differences among SP-A genotypes. The acute phase response (APR) that includes the NF-kB signaling pathway plays a critical role, followed by Nrf2-mediated oxidative response, and others. These associated with SP-A genotype, sex, and ozone-induced oxidative stress in response to infection. We concluded that human SP-A2 and SP-A1 exhibit differential genotype-and sex-dependent innate immune responses to microbial pathogens and/or ozone-induced oxidative stress by modulating proteomic patterns and signaling pathways in the lung.